ABCC5 Transporter is a Novel Type 2 Diabetes Susceptibility Gene in European and African American Populations. (September 2014) - Direk, Kenan; Lau, Winston; Small, Kerrin S.; Maniatis, Nikolas; Andrew, Toby
Summary Numerous functional studies have implicated PARL in relation to type 2 diabetes (T2D). We hypothesised that conflicting human association studies may be due to neighbouring causal variants being in linkage disequilibrium (LD) with PARL. We conducted a comprehensive candidate gene study of the extended LD genomic region that includes PARL and transporter ABCC5 using three data sets (two European and one African American), in relation to healthy glycaemic variation, visceral fat accumulation and T2D disease. We observed no evidence for previously reported T2D association with Val262Leu or PARL using array and fine‐map genomic and expression data. By contrast, we observed strong evidence of T2D association with ABCC5 (intron 26) for European and African American samples (P = 3E−07) and with ABCC5 adipose expression in Europeans [odds ratio (OR) = 3.8, P = 2E−04]. The genomic location estimate for the ABCC5 functional variant, associated with all phenotypes and expression data (P = 1E−11), was identical for all samples (at Chr3q 185, 136 kb B36), indicating that the risk variant is an expression quantitative trait locus (eQTL) with increased expression conferring risk of disease. That the association with T2D is observed in populations of disparate ancestry suggests the variant is a ubiquitous risk factor for T2D.